2001
DOI: 10.1161/hh1401.093293
|View full text |Cite
|
Sign up to set email alerts
|

UT-A Urea Transporter Protein in Heart

Abstract: Abstract-Urea transporters have been cloned from kidney medulla (UT-A) and erythrocytes (UT-B). We determined whether UT-A proteins could be detected in heart and whether their abundance was altered by uremia or hypertension or in human heart failure. In normal rat heart, bands were detected at 56, 51, and 39 kDa. In uremic rats, the abundance of the 56-kDa protein increased 1.9-fold compared with pair-fed, sham-operated rats, whereas the 51-and 39-kDa proteins were unchanged. We also detected UT-A2 mRNA in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Western analysis shows that rat heart expresses 3 UT-A proteins: 56, 51, and 39 kD (7). Uremia increases the abundance of the 56-kD UT-A glycoprotein (7). The abundance of the 56-kD UT-A protein also increases in hypertrophic hearts from non-uremic DOCA/salt hypertensive rats, and in short-term hypertension induced by a 3 d infusion of angiotensin II (7).…”
Section: Heartmentioning
confidence: 96%
See 3 more Smart Citations
“…Western analysis shows that rat heart expresses 3 UT-A proteins: 56, 51, and 39 kD (7). Uremia increases the abundance of the 56-kD UT-A glycoprotein (7). The abundance of the 56-kD UT-A protein also increases in hypertrophic hearts from non-uremic DOCA/salt hypertensive rats, and in short-term hypertension induced by a 3 d infusion of angiotensin II (7).…”
Section: Heartmentioning
confidence: 96%
“…Somewhat surprisingly, heart also expresses a urea transporter (7). Although the rationale is not as obvious as for kidney, red blood cells, or liver, cardiac hypertrophy is associated with an increase in polyamine synthesis (7).…”
Section: Heartmentioning
confidence: 99%
See 2 more Smart Citations
“…In the heart, it has been suggested that urea can have cardioprotective effects in both rat and dogfish, and thus the presence of UTs in the heart under normal conditions may be advantageous . Furthermore, in mammals, there is an upregulation of cardiac UT expression in pathologies promoting urea production in this tissue, such as an increased polyamine synthesis in the development of cardiac hypertrophy (Duchesne et al, 2001). …”
Section: Other Tissuesmentioning
confidence: 99%